Autologous Stem Cell Transplantation for the Treatment of Neuroblastoma in Korea - Ryu, Kyung Ha; Ahn, Hyo Seop; Koo, Hong Hoe; Kook, Hoon; Kim, Moon Kyu; Kim, Hack Ki; Ghim, Thad; Moon, Hyung Nam; Seo, Jong Jin; Sung, Ki Woong; Shin, Hee Young; Yoo, Eun-Sun; et al. (Journal of Korean medical science, 2003)
Autologous stem cell transplantation (ASCT) for the treatment of high-risk neuroblastoma (NBL) is an accepted method for restoring bone marrow depression after high dose chemotherapy. We retrospectively analyzed eighty eight cases of NBL that underwent ASCT following marrow ablative therapy at 12 transplant centers of the Korean Society of Pediatric Hematology-Oncology between January 1996 and September 2000. Seventy nine children were of stage IV NBL and 9 were of stage III with N-myc amplification. Various cytoreductive regimens were used. However, the main regimen was 'CEM' consisting of carboplatin, etoposide and melphalan, and this was used in 66 patients. Total body irradiation was also added in 36 patients for myeloablation. To reduce tumor cell contamination, stem cell infusions after CD34+ cell selection were performed in 16 patients. Post-transplantation therapies included the second transplantation in 18 patients, interleukin2 therapy in 45, 13-cis retinoic acid in 40, 131-meta-iodobenzylguanidine in 4, conventional chemotherapy in 11, and local radiotherapy in 8. Twenty two patients died, sixty six patients are surviving 1 to 46 months after ASCT (median followup duration, 14.5 months). Although the follow-up period was short and the number of patients small, we believe that ASCT might improve the survival rate in high-risk NBL.